STUDENT’S LEARNING INTEREST AND LEARNING OUTCOMES IN HISTORY LESSON - Suhartini, Dewi (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2010)
The research is experimental study of senior high school students in Bogor focuses on the use of e-learning in teaching history and aimed at investigating whether there is any improvement in the student’s interest and learning outcomes in history lesson on the students who learn by e-learning, compared to those who learn by traditional method. Nonequivalent (pretest and posttest) control group design is used in conducting the research. The population is the senior high school students in Bogor. The result shows that the students who learn history by e-learning achieved higher degree than those who do not learn using e-learning method, statistically significant at p0.05. Furthermore, the score of the students learning outcomes for those who learned through e-learning is significantly improved, compared to those who do not learn using e-learning, statistically significant at p0.05. The social economy status is not significantly correlated to the students’ interest and the students’ history learning outcomes. In fact, the students’ skill in using computer showed a significant correlation to the students’ interest and out come at p0.05. It was concluded that the use of e-learning in teaching history is significantly affecting the students’ interest in learning history and the student learning outcomes.